Maternal experience of intimate partner violence is associated with suboptimal breastfeeding practices in Malawi, Tanzania, and Zambia: insights from a DHS analysis - Christine N. Walters; Hasina Rakotomanana; Joel J. Komakech; Barbara J. Stoecker (BMC, 2021)
Abstract Background Despite widespread suboptimal breastfeeding practices and maternal experiences of intimate partner violence (IPV), the association of IPV and breastfeeding practices remains unclear. This study investigated the associations between maternal experience of physical, sexual, emotional violence, and controlling behaviors with suboptimal breastfeeding practices in Malawi, Tanzania, and Zambia. Methods Data included mother-infant dyads from the most recent Demographic and Health Surveys for Malawi (n = 1878), Tanzania (n = 3184), and Zambia (n = 3879). Intimate partner violence (physical, sexual, and emotional) was measured using the Revised Conflict Tactics Scale. Breastfeeding practices were early initiation of breastfeeding (within 1 h of birth), exclusive breastfeeding (in previous 24 h), and continued breastfeeding. Associations between experience of physical, sexual, or emotional violence or controlling behaviors and breastfeeding practices, as well as associations between the frequency of IPV and breastfeeding practices were assessed. Results Many Malawian (77.6%) and Zambian (67.7%) and just over half (53.6%) of Tanzanian mothers, initiated breastfeeding within 1 h of birth. Exclusive breastfeeding was 70.6% in Zambia and 60.1% in Malawi, while 55.0% of Tanzanian mothers breastfed exclusively. Continued breastfeeding to at least 1 year was high in Malawi 92.2%, Tanzania 93.4%, and Zambia 95.0%. Most mothers reported experiences of IPV in Tanzania 79.1%, Zambia 78.9%, and Malawi 73.9%. Mothers who experienced sexual IPV were significantly more likely to delay breastfeeding (Malawi [AOR 1.55 (1.14, 2.10)]; Tanzania [AOR 1.30 (1.04, 1.62)]; and Zambia [AOR 1.28 (1.06, 1.54)]). Sexual IPV in Malawi and Zambia was associated with greater odds of not exclusively breastfeeding (Malawi [AOR 1.90 (1.05, 3.45)]; Zambia [AOR 1.75 (1.15, 2.67)]). Tanzanian mothers who experienced IPV often or sometimes were two times more likely not to breastfeed at one-year post-delivery [AOR 2.23 (1.09,4.57)]. Conclusions In the three countries investigated maternal experience of IPV was associated with suboptimal breastfeeding practices. Policies and programs targeting improved breastfeeding practices should consider screening during antenatal and postnatal care for experience of violence and support initiatives to reduce IPV.